2021
DOI: 10.1016/j.annonc.2021.07.008
|View full text |Cite|
|
Sign up to set email alerts
|

Pembrolizumab for locally advanced and recurrent/metastatic cutaneous squamous cell carcinoma (KEYNOTE-629 study): an open-label, nonrandomized, multicenter, phase II trial

Abstract: Background: Pembrolizumab demonstrated clinically meaningful and durable antitumor activity with a manageable safety profile in recurrent/metastatic (R/M) cutaneous squamous cell carcinoma (cSCC). Patients and methods: KEYNOTE-629 was a global, open-label, nonrandomized, phase II trial of patients with locally advanced (LA) or R/M cSCC conducted at 59 centers. Eligible patients received intravenous pembrolizumab 200 mg every 3 weeks for up to 35 cycles. Primary endpoint was objective response rate (ORR), defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 22 publications
7
103
0
4
Order By: Relevance
“…Post-hoc exploratory analysis of this cemiplimab study also showed symptomatic benefit with improvements in health-related quality of life and pain control ( 36 ). Similarly, the Phase II KEYNOTE-629 study with pembrolizumab reported an ORR of 50% in the locally advanced cohort and 35.2% in the recurrent/metastatic cohort, including a 16.7% and 10.5% CR rate, respectively ( 37 ). The median DOR was not reached in either cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Post-hoc exploratory analysis of this cemiplimab study also showed symptomatic benefit with improvements in health-related quality of life and pain control ( 36 ). Similarly, the Phase II KEYNOTE-629 study with pembrolizumab reported an ORR of 50% in the locally advanced cohort and 35.2% in the recurrent/metastatic cohort, including a 16.7% and 10.5% CR rate, respectively ( 37 ). The median DOR was not reached in either cohort.…”
Section: Discussionmentioning
confidence: 99%
“…CR and PR were observed in 20 and 44 treated patients, respectively. One hundred ten patients reported drug-related AEs with pruritus being the most represented one ( n = 29) [ 52 ].…”
Section: New Emerging Therapies For Advanced Bccmentioning
confidence: 99%
“…In the la-cSCC cohort, the objective RR was 50.0% (95% CI, 36.1% to 63.9%), with 16.7% of patients achieving a CR and 33.3% a PR. In the recurrent or metastatic cSCC cohort, the objective RR was 35.2% (95% CI, 26.2% to 45.2%), including 10.5% of patients with CR and 24.8% with PR [ 62 , 63 ]. Moreover, the phase II CARSKIN trial (NCT02883556), involving 57 patients with unresectable cSCC, showed comparable results, with an objective RR of 42% (95% CI: 29–56%) and DCR of 60% (95% CI: 46–72%) [ 64 , 65 ].…”
Section: The Role Of Immunotherapy In Non-melanoma Skin Cancermentioning
confidence: 99%